2001
DOI: 10.1046/j.1442-2050.2001.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein in esophageal mucosa of individuals at high risk of squamous cell carcinoma of the esophagus

Abstract: Squamous cell carcinoma of the esophagus (SCCE) is diagnosed late and carries a poor prognosis. Biomarkers such as p53 protein expression may be present in the esophageal mucosa long before esophageal symptoms or lesions appear and may point toward early diagnosis. Asymptomatic subjects at high risk for SCEE (consumption of more than 80 g of ethanol and 10 cigarettes/day for at least 10 years) underwent upper gastrointestinal endoscopy with biopsies of the esophageal mucosa, and expression of p53 protein was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
15
1
1
Order By: Relevance
“…In the present study we found few cases of dysplasia/carcinoma; however, a quarter of the subjects studied expressed p53 protein in their esophageal mucosa associated with the severity of the histologic findings, as previously reported by Fagundes et al 21 and Ohbu et al 30 Contrary to our expectations there was no identification of p53 protein expression in cytologic smears. The negative expression of p53 protein in cytologic samples from individuals with positive expression in biopsies produced 2 questions: (1) Were cytologic smears adequate material in which to look for p53 protein expression?…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In the present study we found few cases of dysplasia/carcinoma; however, a quarter of the subjects studied expressed p53 protein in their esophageal mucosa associated with the severity of the histologic findings, as previously reported by Fagundes et al 21 and Ohbu et al 30 Contrary to our expectations there was no identification of p53 protein expression in cytologic smears. The negative expression of p53 protein in cytologic samples from individuals with positive expression in biopsies produced 2 questions: (1) Were cytologic smears adequate material in which to look for p53 protein expression?…”
Section: Discussioncontrasting
confidence: 56%
“…On the basis of the results of Fagundes et al, 21,22 we calculated that it would require 134 patients to detect a 17% positivity of p53 expression in esophageal mucosa of high-risk individuals, considering a statistical power of 90% and a confidence interval of 95%. Data analysis was conducted with SPSS (Chicago, Illinois, U.S.A.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Implicated genes including those involved in cell signalling, cell cycle control, cell adhesion and apoptosis are well characterised and their expression levels are known to be altered in oesophageal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%